Cue hierarchy for host plant selection in Pieris rapae. Issue 4 (18th March 2019) - Lund, Margaret; Brainard, Daniel C.; Szendrei, Zsofia
Abstract: During oviposition, female insects utilize a wide variety of cues to find an optimal host for their offspring. These cues may be encountered simultaneously or sequentially, and females must rely on a hierarchical categorization to rank cues for optimal ovipositional choice. During alighting, cues are often encountered at different distances, which may influence hierarchical order. Cues that are observed at longer distances and are experienced first may be more influential on oviposition choice than those experienced at shorter distances. We tested the effects of two long‐distance cues, plant size and habitat structure, and two short‐distance cues, plant nitrogen level and predator presence, on Pieris rapae L. (Lepidoptera: Pieridae) oviposition choice through a series of two‐ and four‐choice tests in both greenhouse and field settings. We found that the long‐distance cues of plant size and habitat structure had the largest impact on P. rapae oviposition in laboratory and field settings, with females preferring large plants without habitat structure. Plant nitrogen level had a smaller impact on oviposition, and the presence of predators did not affect oviposition choice. However, plant size and plant nitrogen level had a synergistic relationship, with more eggs laid on large high‐nitrogen plants compared to large low‐nitrogen or small high‐nitrogen plants, suggesting that optimal cues throughout the entire searching process may be important for P. rapae in choosing a host plant. Abstract : During oviposition, female insects utilize a wide variety of cues to find an optimal host for their offspring. Long‐distance cues (plant size and habitat structure) had a larger impact on host finding in Pieris rapae (Lepidoptera: Pieridae) than short‐distance cues (plant nitrogen level and predator presence). However, a synergy of optimal long‐ and short‐distance cues may have the largest influence on female oviposition.